Comparative RNA-sequencing profiled the differential gene expression of liver in response to acetyl-CoA carboxylase inhibitor GS-0976 in a mouse model of NASH - Lu, Ying (PeerJ, 2019)
BACKGROUND: Non-alcoholic steatohepatitis (NASH) is a progressive liver disease characterized by hepatic steatosis, lobular inflammation and fibrosis. Acetyl-CoA carboxylase (ACC) isoform 1 and 2 involved in de novo lipogenesis (DNL) and fatty acid oxidation have been identified as a therapeutic target in NASH. GS-0976, the inhibitor of ACC1 and ACC2, has achieved favorable therapeutic effects in clinical trials with NASH. The purpose of this study was to explore the transcriptional alterations regulated by GS-0976 in NASH. METHODS: C57BL/6 mice were fed on a choline-deficient, L-amino acid-defined, high-fat diet (CDAHFD) or normal diet for 12 weeks. Mice were treated with or without GS-0976 (3 mg/kg per day) in the last 8 weeks. Oil Red O, Haematoxylin-eosin (H & E), and Sirius Red were used to evaluate hepatic steatosis, inflammation and fibrosis. The comparative RNA-sequencing was conducted to analyse the hepatic gene expression profiles in mice. Reverse transcription–polymerase chain reaction analysis was performed to validate the differential expression of representative genes. RESULTS: GS-0976 attenuated the steatosis, inflammation, and fibrosis of NASH in CDAHFD mouse model. High-throughput sequencing and differential gene expression analysis showed that there were 516 up-regulated genes and 525 down-regulated genes after GS-0976 treatment. Genes involved in the metabolic process, extracellular matrix formation, immune response, and angiogenesis were significantly enriched. The “Metabolic pathways” and “ECM-receptor interaction” pathways were the most significantly enriched KEGG pathways in the up-regulated and down-regulated differentially expressed genes (DEGs), respectively. CONCLUSIONS: Transcriptome analysis showed that GS-0976 could regulate the expression of genes related to metabolism, inflammation and fibrosis in NASH. The global transcriptomic changes in gene expression promote the further understanding for the inhibition mechanisms of GS-0976 in NASH.